Lectin Protein Spodoptera litura Activity After Exposured by Biopesticide from Mirabilis jalapa - Dina Maulina; Sutiman B Sumitro; Muhammad Amin; Sri Rahayu Lestari (International Journal of Applied Biology, 2019)
Spodoptera litura is folifagus agricultural pest with a tendency of resistance towards chemistry compound. This becomes a reason in the efforts to overcome it. The use of botanical material becomes one of the alternatives in controlling its population. The plant of Mirabilis jalapa has the active biopesticide compound that becomes its alternative prevention. This plant has the potential chemistry compound as biopesticide which works toward weakening immunity that is ended by the death of S. litura.  This research aims to analyze the existence of lectin protein as an indicator of immunity reaction’s activation Spodoptera litura after exposing biopesticide M. jalapa. Lectin test was conducted by using spot-test hemagglutination assay (HA) then was seen its speed forming of titer. The result of research shows that lectin was on the part of hemolimf S. litura supernatant. The result test shows that on the concentration 0.2% binding of lectin, carbohydrate and erythrocyte cells of vertebrate formed faster. The speed of titer forming was influenced by the number of hemosit. This is caused by immulectin receptors were on the cell’s surface. Therefore, exposing M. jalapa can induce lectin activation which functioned as the recognizing receptor of strange object which directly bound with carbohydrate related to the reaction of body immunity.Key words: biopesticide Mirabilis jalapa, lectin, immunity system, Spodoptera litura.